2002
DOI: 10.1093/hmg/11.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Distinct subcellular expression of endogenous polycystin-2 in the plasma membrane and Golgi apparatus of MDCK cells

Abstract: Polycystin-2 is a predicted integral membrane protein with non-selective cation channel activity. The protein is encoded by the PKD2 gene, which is mutated in approximately 15% of patients with autosomal dominant polycystic kidney disease (ADPKD). Polycystin-2 can interact with the transmembrane protein polycystin-1, the product of the PKD1 gene. However, endoplasmic reticulum (ER) localization was reported for (heterologously expressed) polycystin-2 in cultured cells and baso-lateral localization has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 45 publications
5
52
1
Order By: Relevance
“…This hypothesis was supported by several observations, as follows: first, the substantial colocalization of GPNMB with ␤-COP, a protein that associates with membranes of the Golgi complex (29); second, GPNMB staining was dispersed into the ER and endosomal compartments when the Golgi network was disrupted by BFA treatment. GPNMB localization to the Golgi apparatus is also consistent with evidence that GPNMB is a highly glycosylated protein (28,37) and that it contains a polycystic kidney diseases domain that is shared with the polycystin family of vesicle-trafficking mediators (44). Differences in the distribution of GPNMB-and transGolgi-derived vesicles containing the soluble N-ethylmaleimidesensitive factor attachment protein receptor proteins Stx6 and Vti1b (data not shown) suggested that GPNMB may be predominantly associated with cis-Golgi membranes.…”
Section: Discussionsupporting
confidence: 81%
“…This hypothesis was supported by several observations, as follows: first, the substantial colocalization of GPNMB with ␤-COP, a protein that associates with membranes of the Golgi complex (29); second, GPNMB staining was dispersed into the ER and endosomal compartments when the Golgi network was disrupted by BFA treatment. GPNMB localization to the Golgi apparatus is also consistent with evidence that GPNMB is a highly glycosylated protein (28,37) and that it contains a polycystic kidney diseases domain that is shared with the polycystin family of vesicle-trafficking mediators (44). Differences in the distribution of GPNMB-and transGolgi-derived vesicles containing the soluble N-ethylmaleimidesensitive factor attachment protein receptor proteins Stx6 and Vti1b (data not shown) suggested that GPNMB may be predominantly associated with cis-Golgi membranes.…”
Section: Discussionsupporting
confidence: 81%
“…A number of different localizations of the PCs have been proposed, including localization to the ER (likely a major site of PC2) or to the apical and basolateral membranes, or secretion on microvesicles (exosomes) (56,58,59). Although these localizations are likely, there are several lines of evidence that primary cilia are central to pathogenesis in PKD, making it a ciliopathy (3).…”
Section: Figurementioning
confidence: 99%
“…Given that Pkd2 is expressed ubiquitously, Pkd2 may potentially function during LR patterning at any site between, and including, the node and LPM. The subcellular localization of Pkd2 has also been controversial, as it has been detected in association with a variety of organelles, including the plasma membrane, Golgi apparatus (Scheffers et al, 2002), mitotic spindle (Rundle et al, 2004) and cilia (Yoder et al, 2002). If it is localized to the surface of node cilia, Pkd2 may serve as a mechanosensory, as proposed by the two-cilia model (McGrath et al, 2003;Tabin and Vogan, 2003), which proposes that two kinds of node cilia exist in the node: motile cilia that are positive for a dynein called Lrd (Supp et al, 1997), which generate the flow; and immotile Lrd-negative cilia, which presumably act as mechanosensors.…”
Section: Role Of a Ca 2+ Signalmentioning
confidence: 99%